Estimation of Moisture Content of Oil Palm Fronds through Correlation with Density for the Process of Gasification - Shaharin Anwar, Sulaiman; Guangul, Fiseha Mekonnen; Konda, Ramzy E.; Atnaw, Samson M.; Mohamad Nazmi, Moni (North Carolina State University, 2016)
In the gasification process, one prominent factor that affects the quality of the resulting syngas is the moisture content of the biomass feedstock. Determining the moisture content of a feedstock is considered to be one of the challenges of the process. The information about moisture content of a feedstock is required to decide the need for further drying prior to the gasification process. In this study, a novel method was developed for the evaluation of the moisture content from density of oil palm fronds (OPF) in a sufficiently accurate manner for gasification process. A total of 147 samples from different sections of freshly pruned fronds were prepared. The density of each of the samples was determined from its weight and volume. A fine sand displacement method, using fine sand and a graduated cylinder, determined the volume of OPF. The moisture content of the OPF was determined from the weight difference of the samples before and after the drying process. The experiment implied a good correlation between moisture content and density of the biomass, in which the square of the correlation coefficient (R2) value was found to be satisfactory.